The corticotroph cells from early development to tumorigenesis. (7th May 2022) - Drouin, Jacques
Abstract: During development, highly specialized differentiated cells, such as pituitary secretory cells, acquire their identity and properties through a series of specification events exerted by transcription factors to implement a unique gene expression program and epigenomic state. The investigation of these developmental processes informs us on the unique features of a cell lineage, both to explain these features and also to outline where these processes may fail and cause disease. This review summarizes present knowledge on the developmental origin of pituitary corticotroph and melanotroph cells and on the underlying molecular mechanisms. At the onset, comparison of gene expression programs active in pituitary progenitors compared to those active in differentiated corticotrophs or melanotrophs indicated dramatic differences in the control of, for example, the cell cycle. Tpit is the transcription factor that determines terminal differentiation of pro‐opiomelanocortin (POMC) lineages, both corticotrophs and melanotrophs, and its action involves this switch in cell cycle control in parallel with activation of cell‐specific gene expression. There is thus far more to making a corticotroph cell than just activating transcription of the POMC gene. Indeed, Tpit also controls implementation of mechanisms for enhanced protein translation capacity and development of extensive secretory organelles. The corticotroph cell identity also includes mechanisms responsible for homotypic cell–cell interactions between corticotrophs and for privileged heterotypic cell interactions with pituitary cells of other lineages. The review also summarizes current knowledge on how a pioneer transcription factor, Pax7, remodels the epigenome such that the same determination transcription factor, Tpit, will implement the melanotroph program of gene expression. Finally, this canvas of regulatory mechanisms implementing POMC lineage identities constitutes the background to understand alterations that characterize corticotroph adenomas of Cushing's disease patients. The integration of all these data into a unified scheme will likely yield a scheme to globally understand pathogenic mechanisms in Cushing's disease.